Desenvolvimento de revestimentos anódicos de TiO2 funcionalizados com fosfato de cálcio e ranelato de estrôncio para aplicações odontológicas - Ana Paula dos Reis Weitzel (2023)
Titanium and its alloys are widely used in the manufacture of dental implants due to their chemical, biological, and mechanical stability. Currently, the predominant titanium surface in implant dentistry is SLA, which is obtained by sandblasting and acid treatment. However, this surface has disadvantages both in the production process and in the possibility of fibrous capsule formation around the devices, which can lead to the loss of the implant. Recent literature reports that a nanotubular layer of TiO2 (NT) formed on metallic titanium is a good alternative because it provides a larger bone-implant contact surface and accelerates the osseointegration process, resulting in a shorter patient recovery time. Thus, functionalization of the NT layer with calcium phosphate (CaP) compounds is common due to its similarity to bone mineral composition, but comparative studies between functionalized NT and the SLA surface are still rare in the literature. In addition to CaP, the use of strontium ranelate (SrR), a drug used in the treatment of osteoporosis that acts mainly by reducing bone resorption, as a functionalization is interesting. This work dealt with the fabrication, characterization, and functionalization of SLA and NT surfaces with CaP compounds and strontium ranelate, and the results were presented in two chapters. The first chapter deals with the study of the morphological and chemical properties of these surfaces before and after the deposition of CaP by the chemical conversion method. The second chapter includes a comparative study between the NT surface as produced and depositions with CaP, SrR, and a combination of these substances (CaP+SrR). Both studies evaluated the efficacy of the coatings and their biological effects in vitro. Furthermore, a comparison between deposited NT surfaces with CaP, SrR, and CaP + SrR has not been reported in the literature. The results indicated that the deposition was successful and that the functionalized surfaces are promising candidates for dental use, showing high cell viability, differentiation, and mineralization.